Defense Diplomacy in Peacekeeping Missions: A Comparative Analysis of the United States And India - Sejati, Maulidiyah Dewi; Pedrason, Rodon; Inkiriwang, Frega Wenas (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2024)
Defense diplomacy, better known as military diplomacy, is the nonviolent use of military force to advance a country's diplomatic relations and promote its international agenda. This research aims to investigate the practice of the use of defense diplomacy by the United States and India in peacekeeping missions, particularly those under UN mandates. Through a qualitative approach, this research analyzes a case study through a literature review. The research findings highlight the importance of defense diplomacy in achieving national interests through peacekeeping missions and identify key factors that influence its effectiveness, such as military capacity and capability, interagency cooperation and the formulation of diplomatic strategies. The results provide important insights into the role of defense diplomacy in the context of international relations and its potential to enhance the effectiveness of diplomacy.